2015
DOI: 10.1016/j.clay.2015.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Montmorillonite colloids: I. Characterization and stability of dispersions with different size fractions

Abstract: Bentonite is planned to be used as a technical barrier in the final storage of spent nuclear fuel and high level vitrified waste. In contact with ground water of low ionic strength, montmorillonite colloids may be released from the bentonite buffer and thereby enhance the transport of radionuclides (RNs) sorbed. In the present case, clay colloids represent aggregates of several clay mineral layers. It is of major importance to determine RN sorption properties for different sizes of montmorillonite aggregates, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 70 publications
2
21
0
1
Order By: Relevance
“…Taking the intersection at W = 1 as calcium critical coagulation concentration in presence of fulvic acids (Ca/FA-CCC) for pH 10, only a marginal increase can be detected, which is within the analytical uncertainty. This observation is in line with measurements of Norrfors et al [19], who could not determine a change in colloid stability by addition of GoHy-573FA to MX-80 bentonite colloids. However, at lower pH values, an increase in the Ca/FA-CCC to values ≤2 mmol L −1 could be determined, and therefore 2 mmol L −1 was taken as Ca/FA-CCC.…”
Section: Colloid Stabilitysupporting
confidence: 92%
See 1 more Smart Citation
“…Taking the intersection at W = 1 as calcium critical coagulation concentration in presence of fulvic acids (Ca/FA-CCC) for pH 10, only a marginal increase can be detected, which is within the analytical uncertainty. This observation is in line with measurements of Norrfors et al [19], who could not determine a change in colloid stability by addition of GoHy-573FA to MX-80 bentonite colloids. However, at lower pH values, an increase in the Ca/FA-CCC to values ≤2 mmol L −1 could be determined, and therefore 2 mmol L −1 was taken as Ca/FA-CCC.…”
Section: Colloid Stabilitysupporting
confidence: 92%
“…It is determined by means of the stability ratio W, which is defined as the fastest coagulation rate r fast of single colloid to doublet formation in the system of interest (purely diffusion-controlled aggregation) to the actual coagulation rate of doublet formation r actual [17,18]. A stability ratio is colloid-size-independent [19]. The critical coagulation concentration (CCC) refers to the [Me + ] or [Me 2+ ] concentration at the transition of fast, purely diffusion-controlled to slow coagulation.…”
Section: Introductionmentioning
confidence: 99%
“…These parameters should therefore be included in reactive transport modelling. In a recent study on montmorillonite colloidal stability performed at various ionic strengths (Norrfors et al, 2015), no dependency on the montmorillonite size could be observed. Based on this study, hydrodynamic induced size fractionation and the potential formation of different colloid size fractions will not influence their stability under the same geochemical conditions but some colloids may be able to migrate further due to e.g.…”
Section: Introductionmentioning
confidence: 91%
“…Given the same density of all clay particles, the amount of edge sites are proportional to the aspect ratio. This model was further developed by the authors in a previous work (Norrfors et al, 2015) where montmorillonite colloids were successfully separated into fractions with varying mean colloid sizes. These colloids were used in the adsorption study presented in this work.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it plays an important role in many geological processes, the phenomena of the petroleum migration, greenhouse gas sequestration, oilfield [3], and in engineering. Moreover, for last decades, the smectites were widely used as crucial components for elaboration of natural barriers to isolate the hazardous wastes and for the removal of heavy metal cations from various effluents of industrial and wastewater treatment [4][5][6][7][8][9][10][11][12] and also proposed as geotechnical barriers in many nuclear waste disposal concepts in order to retard the potential transport of radionuclides towards the biosphere [13][14][15].…”
Section: Introductionmentioning
confidence: 99%